Policing along the spectrum: Reducing risk and improving service delivery - Leydier, Thomas B (International journal of police science & management, 2022)
Autism spectrum disorder is a complex life-long neurodevelopmental disorder that affects social skills, language, learning, cognitive function, physical abilities, and behavior. Moreover, autism is becoming increasingly prevalent in Canada and abroad. Inevitably, law enforcement professionals will interact with the autistic population in their duties; however, many exchanges produce poor outcomes. Physical restraint is often used, and the benefit of autism-trained Crisis Intervention Teams is underutilized, especially in Canada. In addition, current training outcomes for law enforcement professionals are ephemeral and unlikely to yield mastery. This article argues three antidotes to improve service delivery and reduce risk: Crisis Intervention Teams that incorporate autism training; methodologically sound and rigorously evaluated practical training; and community outreach, which creates relationships proactively and fosters trust. Future research should: analyze the outcomes of autistic-trained Crisis Intervention Teams; determine qualitatively what the population with autism and their stakeholders seek in a comprehensive training curriculum; and determine the success of nascent training courses and community outreach goals.